2021
DOI: 10.1038/s41390-021-01423-8
|View full text |Cite
|
Sign up to set email alerts
|

Age-related changes in the inflammatory responses to viral infections in the central nervous system during childhood

Abstract: BACKGROUND: The developmental stages and function of immune cells in the central nervous system during infancy and childhood are poorly understood. We analyzed whether cytokine and chemokine profiles in children and adolescents with viral central nervous system infections were different depending on age. METHODS: The acute phase cerebrospinal fluid of 80 children (mean age 98 months, range 1-206 months) were analyzed for protein levels of interleukin-1β (IL-1β),

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“… 156 In this study, CSF expression of IL-4 and IL-13 was found to increase with age in response to viral infections, suggesting their importance in the risk of developing of long-term sequelae. 168 In their study, Silva et al found that IL-4 knockout mice with experimentally induced neurocysticercosis had lower cerebral edema, lower inflammatory infiltrates and prolonged survival of the parasites in the brain. 169 This indicates that IL-4 is preferentially expressed in response to infections in an attempt to reduce brain damage, possibly explaining the previous observations that asymptomatic patients from endemic areas exhibit increased production of IL-4 and IL-13.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“… 156 In this study, CSF expression of IL-4 and IL-13 was found to increase with age in response to viral infections, suggesting their importance in the risk of developing of long-term sequelae. 168 In their study, Silva et al found that IL-4 knockout mice with experimentally induced neurocysticercosis had lower cerebral edema, lower inflammatory infiltrates and prolonged survival of the parasites in the brain. 169 This indicates that IL-4 is preferentially expressed in response to infections in an attempt to reduce brain damage, possibly explaining the previous observations that asymptomatic patients from endemic areas exhibit increased production of IL-4 and IL-13.…”
Section: Discussionmentioning
confidence: 96%
“… 153 , 154 The exact effect of IL-33 on the remyelination of MS lesions is also controversial, some studies indicating inhibition of CNS myelination, while others indicate favoring of myelin repair. 153–155 , 168 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To advance this research direction, it is essential to conduct a thorough characterization of not only Th1/Th2 cytokines but also Th9/Th17/Th22/Treg cytokines and chemokines during LACV infection. The investigation of cytokine profiles becomes particularly crucial in the context of age-dependent viral infections infiltrating the central nervous system (CNS) (24). This study demonstrated that cytokine and chemokine profiles in children and adolescents with tick-borne encephalitis vary depending on age (24).…”
Section: Discussionmentioning
confidence: 99%
“…The investigation of cytokine profiles becomes particularly crucial in the context of age-dependent viral infections infiltrating the central nervous system (CNS) (24). This study demonstrated that cytokine and chemokine profiles in children and adolescents with tick-borne encephalitis vary depending on age (24). Such variability in cytokine and chemokine responses may significantly influence the outcome of viral infections and the subsequent risk of severe disease outcomes.…”
Section: Discussionmentioning
confidence: 99%